Prelalência dos subtipos virais 16 e 18 de papilomavirus humano (HPV) em mulheres da cidade de Manaus /AM - Silva, Alessandra Silva e (2017)
The natural history of cervical cancer is strongly related to the presence of papillomavirus (HPV) infection, its relation with cervical cancer is worrisome because one in each four women has virus contamination. It is estimated that 70% of all cervical cancers in the world are caused by HPV 16 and 18. Thus, the realization of this study aimed to contribute to identifying the viral subtypes of circulating HPV in the population of Manaus-AM. Was then made the collection of cervical sample of 49 women, within the criteria of eligibility of the study, was made DNA extraction from the samples and analysis of the presence of the virus in the genetic material, by polymerase chain reaction (PCR), using the generic primers (GP05/06), finally, the identification of the viral subtypes present, using specific primers of the major subtypes already studied (16 and 18). Positive HPV-DNA was detected in 100% of the samples included in the study. HPV 16 was the most prevalent type in most lesions with 29 (59.2%) of the positive cases and HPV 18 was detected in 4 (8.2%) women. Multiple infections occurred in 8.2% of cases and infections by other types of HPV were detected in 40.8% of samples. These data have clinical implications when considering an effectiveness in the prevention of Cervical Neoplasms of current prophylactic HPV vaccines, since their coverage, relative to the HPV of oncogenic high risk, is restricted at 16 and 18. Keywords: Cervical cancer; Human papillomavirus; HPV 16; HPV 18; Manaus-AM.